Polydopamine-Assisted Surface Modification of Ti-6Al-4V Alloy with Anti-Biofilm Activity for Dental Implantology Applications - Ioana Cristina Marinas (MDPI AG, 2021)
Coating the surfaces of implantable materials with various active principles to ensure inhibition of microbial adhesion, is a solution to reduce infections associated with dental implant. The aim of the study was to optimize the polydopamine films coating on the Ti-6Al-6V alloy surface in order to obtain a maximum of antimicrobial/antibiofilm efficacy and reduced cytotoxicity. Surface characterization was performed by evaluating the morphology (SEM, AFM) and structures (Solid-state 13C NMR and EPR). Antimicrobial activity was assessed by logarithmic reduction of CFU/mL, and the antibiofilm activity by reducing the adhesion of Escherichia coli, Staphylococcus aureus, and Candida albicans strains. The release of NO was observed especially for C. albicans strain, which confirms the results obtained for microbial adhesion. Among the PDA coatings, for 0.45:0.88 (KMnO4:dopamine) molar ratio the optimal compromise was obtained in terms of antimicrobial activity and cytotoxicity, while the 0.1:1.5 ratio (KMnO4:dopamine) led to higher NO release and implicitly the reduction of the adhesion capacities only for C. albicans, being slightly cytotoxic but with moderate release of LDH. The proposed materials can be used to reduce the adhesion of yeast to the implantable material and thus inhibit the formation of microbial biofilms.